Control channel assisted chip equalization for CDMA downlink adaptive modulation and coding system - Gubeskys, A.; Chass, A. (2005 IEEE 61st Vehicular Technology Conference, 2005)
Linear chip equalizers designed especially for the downlink have been a subject of extensive research and various methods have been proposed. In this paper, we consider the equalization problem in adaptive modulation and coding (AMC) system. An inherent feature of an AMC system is a high reliability of control information used for modulation type and coding rate signaling. We propose a linear equalization scheme exploiting this feature. The performance of the method is evaluated in HSDPA 3G cellular link.